2015
DOI: 10.1016/j.rvsc.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of viremia, proviral load and cytokine profile in naturally feline immunodeficiency virus infected cats treated with two different protocols of recombinant feline interferon omega

Abstract: This study assesses viremia, provirus and blood cytokine profile in naturally FIV-infected cats treated with two distinct protocols of interferon omega (rFeIFN-ω). Samples from FIV-cats previously submitted to two single-arm studies were used: 7/18 received the licensed/subcutaneous protocol (SC) while 11/18 were treated orally (PO). Viremia, provirus and blood mRNA expression of interleukin (IL)-1, IL-4, IL-6, IL-10, IL-12p40, Interferon-γ and Tumor Necrosis Factor-α were monitored by Real-Time qPCR. Concurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…Specifically, IL-6 plasma levels decreased and proviral loads increased in FIV-cats treated subcutaneously with rFeIFN-ω, while IL-6 mRNA expression decreased in the oral group. However, the therapy did not affect viremia and the expression of other cytokines (IL-1, IL-4, IL-10, IL-12p40, IFN-γ, and tumor necrosis factor-α) [49]. Thus, IFN-ω appears to be involved in innate immunity, and it could further inhibit viral replication and exert its antiviral activity.…”
Section: Regulating the Innate Immune Responsementioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, IL-6 plasma levels decreased and proviral loads increased in FIV-cats treated subcutaneously with rFeIFN-ω, while IL-6 mRNA expression decreased in the oral group. However, the therapy did not affect viremia and the expression of other cytokines (IL-1, IL-4, IL-10, IL-12p40, IFN-γ, and tumor necrosis factor-α) [49]. Thus, IFN-ω appears to be involved in innate immunity, and it could further inhibit viral replication and exert its antiviral activity.…”
Section: Regulating the Innate Immune Responsementioning
confidence: 93%
“…When cells are treated with IFN-ω, Mx-1, ISG15, IFIT3, and ISG56 expression was upregulated in a dose-dependent or time-dependent manner [20,29]. More recently, studies from Leal et al [49] showed that interleukin (IL)-6 production was affected considerably in feline immunodeficiency virus (FIV)-infected cats treated with recombinant feline IFN-ω (rFeIFN-ω) by subcutaneous or oral protocols. Specifically, IL-6 plasma levels decreased and proviral loads increased in FIV-cats treated subcutaneously with rFeIFN-ω, while IL-6 mRNA expression decreased in the oral group.…”
Section: Regulating the Innate Immune Responsementioning
confidence: 99%
“…IL-6 mRNA expression decreases in an oral group. Viremia and other cytokines (IL-1, IL-4, IL-10, IL-12p40, IFN-γ and TNF-α) do not change with therapy [75]. A previous study showed that cytotoxic effects (e.g.…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
“…These results indicate that the two protocols are probably acting distinctly. Th-1 and Th-2 responses do not significantly change with either protocol, and only levels of IL-6, a pro-inflammatory cytokine involved in different immune pathways, particularly the innate immune response, significantly change in both groups [75]. In cats treated with the licensed protocol, IL-6 plasma levels are significantly reduced.…”
Section: Current Potential Applications Of Type I Ifn Classesmentioning
confidence: 99%
See 1 more Smart Citation